The Impact of Company Size and Liquidity on Firm Value with Profitability as a Moderating Variable (A Study of Property & Real Estate Companies Listed on the IDX in the 2021-2024 Period) - Anis Purwanti; Erwin Budianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of company size and current ratio on company value, as well as the role of profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The research method used is associative quantitative with a Moderated Regression Analysis (MRA) approach. The study population consisted of 92 property and real estate companies, with a sample of 14 companies selected using a purposive sampling technique, resulting in 56 observational data. The data used are secondary data sourced from annual financial reports published on the official IDX website. Company value is measured using Price to Book Value (PBV), company size is measured using the natural logarithm of total assets, the current ratio is measured using the ratio of current assets to current liabilities, and profitability is measured using Return on Assets (ROA). The results of the study indicate that: (1) company size has a significant effect on company value; (2) the current ratio does not have a significant effect on company value; (3) profitability has a significant negative effect on company value; (4) profitability strengthens the effect of company size on company value; and (5) profitability does not moderate the influence of the current ratio on company value.